Implementasi Media Bahan Alam untuk Meningkatkan Kreativitas Seni Rupa Anak Usia Dini - Alyawati, Sulis; Wulansuci, Ghina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2025)
Learning and play activities are essential for developing children's creativity. Children’s fine art creativity cannot develop optimally without appropriate stimulation. Enhancing children's fine art creativity requires varied learning media and innovations that utilize natural materials, which are easy to obtain. This study aimed to examine the process and enhancement of children's artistic creativity through the use of natural material media. This study employed classroom action research using the Kemmis and McTaggart model, involving 18 children in Group B. Data were collected through observation and analyzed using quantitative descriptive methods with percentage calculations. Initially, none of the children were categorized as having very good developmental outcomes. Thus, the use of natural material media in Group B at RA Al-Hidayatul Ilmi was found to be highly effective, as evidenced by the increase in the number of children categorized as having very good developmental outcomes.